Progress in Prevention and Treatment of Acute Bone Loss in Orthopedics - Haoran Wang; Ji Wu; Boyao Wang; Hu Qin; Lei Fan; Yunhua Wang; Bin He (International Journal of Endocrinology)
Orthopedic patients need to perform limb immobilization for several days to several weeks due to fracture or other special circumstances. When the function of a certain part or the whole body is restricted, the activity of osteoclasts will be enhanced and its life activity will surpass that of osteoblasts, so local or even whole body bone loss will occur. Acute bone loss usually occurs within a few weeks after the immobilization of limbs. At this stage, the patient’s bone mass will decrease sharply, and the patient is prone to osteoporotic refracture. After that, the bone mass will gradually recover, but the speed of bone formation and bone absorption is difficult to reach a balanced state, and the bone mass of patients will continue to decline after it has recovered to a certain degree. After acute progressive bone loss, a large number of bones were lost and the strength of bones decreased. It is often difficult to recover to the level before fracture for a long time, which undoubtedly increases the risk of osteoporosis and related refractures. According to this common phenomenon of bone loss, clinical treatment varies greatly. After a series of research and practice, clinicians summed up some rules and put forward some feasible suggestions, thus strengthening clinicians’ understanding of the treatment of acute bone loss, effectively improving the treatment effect of acute bone loss, having far-reaching significance for preventing and treating osteoporosis, reducing the risk of fracture, and improving the long-term prognosis of patients.